Optimal facility–final exit assignment algorithm for building complex evacuation. (July 2015) - Kang, Jihyun; Jeong, In-Jae; Kwun, Joon-Bum
Highlights: The optimal evacuation plan reduces the evacuation time. We propose mathematical models and an optimal algorithm. The evacuation time of the last evacuee is minimized. We compare the proposed models and algorithms with a simulation model. Abstract: In this research, a mathematical model is proposed to solve a facility–final exit assignment problem. In a facility–final exit assignment, "facility" means the sub-space of a building and "final exit" is the exit of the building to outside which applies to the overall building complex and not the facilities. Facilities are assigned to exits such that the average evacuation time of the last evacuee in a large building complex is minimized. This research proposes two mathematical models. The first one is a linear programming model that allows for the split of occupants in a facility so that they can evacuate through multiple exits. The second model is an integer programming model that constrains occupants in one facility to evacuate through a single exit. The proposed linear programming model is more realistic to simulate actual evacuation procedures when emergency events such as a fire or a chemical spill occur. In contrast, the proposed integer programming model is more suitable when the objective of the facility–final exit assignment is to train and guide occupants in building complex in pre-emergency environment assuming that we are under a certain disaster. A case study of a mega shopping mall in Korea indicates that the proposed optimal evacuation plan outperforms the facility–nearest exit assignment solution.